2020
DOI: 10.1007/978-3-030-58147-3_38
|View full text |Cite
|
Sign up to set email alerts
|

2MoTac: Simulation of Button Click by Superposition of Two Ultrasonic Plate Waves

Abstract: Recent studies have shown that a button click sensation could be simulated thanks to ultrasonic vibrations. In this context, a travelling wave may enhance the simulation because it creates internal lateral stresses that are released during the stimulation. However, this solution is difficult to integrate on plates. We present 2MoTac, a method which superpose a longitudinal and a bending mode simultaneously on a plate, in order to create a pseudo-travelling wave. We present the design, and a psychophysical stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…When the stimulation is created only from normal displacement of the surface, the success rate is only 30% with a large Standard deviation (19%). This confirms the study in [8] in which this stimulation principle was found to be very variable from one participant to the other. But interestingly, when introducing the elliptical motion of particles, the participants could distinguish the simulated button with a success rate of 95%.…”
Section: Psycho-physical Studysupporting
confidence: 89%
See 3 more Smart Citations
“…When the stimulation is created only from normal displacement of the surface, the success rate is only 30% with a large Standard deviation (19%). This confirms the study in [8] in which this stimulation principle was found to be very variable from one participant to the other. But interestingly, when introducing the elliptical motion of particles, the participants could distinguish the simulated button with a success rate of 95%.…”
Section: Psycho-physical Studysupporting
confidence: 89%
“…In order to simplify this model, we consider that ω is close to the value at resonance, and we introduce then δω i the deviation from ω i0 to ω, ω = ω i0 + δω i with δω i ω i0 . We can then consider M i + Ki ω 2 ≈ 2M i and Ki ω − M i ω = 2M i δω i , leading the simplified equations (8):…”
Section: Model Projection In the (Dq) Coordinate Systemmentioning
confidence: 99%
See 2 more Smart Citations